2014
DOI: 10.2478/plc-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Effects on Motivation and Attitudes in German Learning: The Polish Context

Abstract: The research investigates the German language learning motivations of Polish secondary school students and university students. Questionnaire data were collected from 247 students (126 from secondary school and 121 from university). The aim of this research was to examine the relationships among language attitudes, instrumental, cultural interest, integrative, L2 self and motivated learning. The results show the existence of age and gender difference in variables under consideration. Relationships were found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
(12 reference statements)
4
18
4
1
Order By: Relevance
“…In the present study, a significant difference between Polish female and male learners of English in terms of their overall motivation was found, with female learners reporting higher levels of motivation than their male peers. These findings are consistent with the previously reported findings in the Polish context (Okuniewski, ) and those from other contexts, such as Japan (Ryan, ), Hungary (Dörnyei & Csizér, ) and Turkey (Öztürk & Gürbüz, ), which also reported the advantage of female over male learners in language learning motivation. At the same time, it needs to be acknowledged that the effect size of the individual differences reported here is small, which means that the results affect only a small proportion of the population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, a significant difference between Polish female and male learners of English in terms of their overall motivation was found, with female learners reporting higher levels of motivation than their male peers. These findings are consistent with the previously reported findings in the Polish context (Okuniewski, ) and those from other contexts, such as Japan (Ryan, ), Hungary (Dörnyei & Csizér, ) and Turkey (Öztürk & Gürbüz, ), which also reported the advantage of female over male learners in language learning motivation. At the same time, it needs to be acknowledged that the effect size of the individual differences reported here is small, which means that the results affect only a small proportion of the population.…”
Section: Discussionsupporting
confidence: 93%
“…In Poland, one of the biggest countries in the European Union (EU), female learners aged 15–16 have been found to score higher than their male peers in the national exam in a foreign language (CKE, , ). However, only one study has investigated gender differences in language learning motivation (Okuniewski, ). Yet this study, like other studies examining gender differences, did not explore how gender might affect the interaction between motivational variables.…”
Section: Introductionmentioning
confidence: 99%
“…It implies that regardless of gender, the respondents showed positive attitudes towards the four languages. This finding contradicts the following studies: Eshghinejad (2016) found that female had significantly higher attitude than the male respondents; Okuniewski (2014) where female respondents were significantly higher than males among secondary students on the aspects of motivation, attitudes, language orientation, certain social relations and specific aspects of the second language; Alaga (2016) who concluded that sex was significantly related to attitude; Gömleksiz (2010) in which females were more positive in their attitudes towards English learning in terms of interest, usefulness and teacher subscales; Kesgin and Arslan (2015) where female group showed more interest, positive behaviour and better performance than male group. The studies of Durer and Sayar (2013) and Huseein, Demiroka and Uzunboylu (2009) reveal similar results to the current study that males and females do not differ in their language attitudes toward English.…”
Section: Discussioncontrasting
confidence: 55%
“…They also expressed their agreement that English makes them globally competitive. This finding is somehow different form the study of Okuniewski (2014) because in this study, the older respondents showed higher positive attitude towards English than the younger ones.…”
Section: Discussioncontrasting
confidence: 53%
“…Regarding the role of gender in L2 pedagogy, early evidence suggests a female advantage at higher levels of motivation, strategy use, comprehension, positive affect, willingness to confront and exposure to authentic input (Bacon & Finnemann, ). Most recently, differences in favor of females have been reported in motivational patterns and attitudes (e.g., Kissau, Kolano, & Wang, ; Mori & Gobel, ; Okuniewski, ), in L2 anxiety (e.g., Park & French, ) and in recruiting native language phonological knowledge during novel word learning (e.g., Kaushanskaya, Marian, & Yoo, ). Despite a female superiority in various L2 tasks, counterevidence is also found.…”
Section: Literature Reviewmentioning
confidence: 99%